2018
DOI: 10.1021/acsenergylett.8b01669
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing and Controlling the Surface Structure and Electronic Passivation of Cesium Lead Halide Nanocrystals

Abstract: Colloidal lead halide perovskite nanocrystals (NCs) have recently emerged as versatile photonic sources. Their processing and luminescent properties are challenged by the lability of their surfaces, i.e., the interface of the NC core and the ligand shell. On the example of CsPbBr3 NCs, we model the nanocrystal surface structure and its effect on the emergence of trap states using density functional theory. We rationalize the typical observation of a degraded luminescence upon aging or the luminescence recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
538
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(565 citation statements)
references
References 95 publications
27
538
0
Order By: Relevance
“…Similarly, CsPbBr 3 nanocrystals showed a shorter first component lifetime of 3.85 ns and a longer second component lifetime of 7.79 ns with relative contribution of 51.5 and 48.5 % respectively. This results also in well agreements with the existing literature report of near unity PLQY of CsPbBr 3 nanocrystals obtained by post synthesis surface treatment ,…”
Section: Figuresupporting
confidence: 93%
“…Similarly, CsPbBr 3 nanocrystals showed a shorter first component lifetime of 3.85 ns and a longer second component lifetime of 7.79 ns with relative contribution of 51.5 and 48.5 % respectively. This results also in well agreements with the existing literature report of near unity PLQY of CsPbBr 3 nanocrystals obtained by post synthesis surface treatment ,…”
Section: Figuresupporting
confidence: 93%
“…As mentioned earlier, the most commonly used ligands for perovskite QDs are OAm and OA. Recently, it has been demonstrated that oleylammonium ions attach to the QD surface by competing with Cs + for the A site cation vacancies on the surface of the QD, while oleate ions attach to the QD surface by competing for the X site anion vacancies . The anion exchange reaction of perovskite QDs starts with the injection of the metal halide (MX 2 ) solution into a solution of CsPbBr 3 QDs.…”
Section: Resultssupporting
confidence: 87%
“…Introduction of conjugated molecules that are strong electron donors or acceptors can be an approach to the formation of long-lived mobile charge carriers. While charge separation may be achieved by adding donor and acceptor molecules in solution 29 , the eventual application in the solid state requires that they contain binding groups with affinity for the nanoplatelets (NPLs) 30 . For example, perylene diimides (PDI) are wellknown electron acceptors used in organic electronics and photovoltaics [31][32][33] .…”
mentioning
confidence: 99%